Employee Performance is Affected by Work Environment and Work Motivation, with Job Satisfaction Acting as a Mediating Variable - Nurkumalasari, Ida; Mustafa, Ikrima M (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2024)
ABSTRACTObjective: The objective of this study is to comprehend and examine the relationship that exists between employee performance, the work environment, and work motivation. Additionally, the role that job satisfaction plays as a mediator in this relationship will be examined. The research population consists of all 67 employees of the Central Statistics Agency Office of Maluku Province.Methodology: The PLS-SEM approach is utilized to analyze the data, and SmartPLS 3.0 software is employed as tool for statistical testing.Findings: At a 5% level of confidence, the hypotheses H1, H2,H4 and H5 are accepted, and the path coefficient values are positive, but H3 and H6 rejected.Conclusion: Employee performance is positively and significantly impacted by work motivation. Employee performance is positively and significantly impacted by the work environment. Employee performance is unaffected by job contentment, while job satisfaction is unaffected by work motivation. The relationship between work motivation and employee performance is not mediated by job satisfaction. The relationship between work environment and employee performance is mediated by job satisfaction, although it is a negative relationship. This indicates that although job satisfaction has a major impact on employee performance, it degrades the link between motivation and work environment.Â